Sistema de control interno para el departamento de bodega de la empresa comercial alejo. - Cordero Ramon, Marcos David; Crow Sanchez, Adrian Emanuel (Machala : Universidad Técnica de Machala, 2024)
The Commercial Company ¨Alejo¨, is dedicated particularly to the wholesale marketing of hardware items; where, when making a deep analysis of the way in which the inventory of the company is being managed, it was evident that there is a lack of control and, therefore, the whole chain of the accounting process is affected. Due to the lack of an internal control system for the warehouse department, these problems in inventorying items not only affect the procedures of the personnel in charge of the warehouses, but also the company's profits at the end of the month and the period of operation. This situation caused the inadequate procedures for the registration of inputs and outputs, in addition to the knowledge of the stock, on the organization's inventories to be determined as the object of the case analysis. For the purposes of this research, it was decided to use a method with a qualitative approach, since, by collecting data and information, the hypotheses become real and verifiable. Based on the field research, it is corroborated that the ¨Alejo¨ Commercial Company does not have an adequate inventory control system, thus generating the proposal of a feasible system for this company, with the purpose of improving the inventory registration procedure, as well as the reduction of expenses under the purpose of strengthening profitability.
La Empresa Comercial ¨Alejo¨, se dedica particularmente a la comercialización al por mayor de artículos de ferretería; donde, al hacer un análisis profundo de la forma en que se está gestionando el inventario de la empresa, quedó en evidencia que existe una carencia de control y, por ende, se ve afectada toda la cadena del proceso contable. Por motivos de inexistencia de un sistema de control interno destinado al departamento de bodega, estos inconvenientes a la hora de inventariar los ítems no solo repercuten en los procedimientos del personal encargado de los almacenes sino también en las utilidades que obtiene la empresa al final del mes y del periodo de operación. Esta situación provocó que se determine como objeto de análisis de caso los procedimientos inadecuados para el registro de entradas y salidas, además del conocimiento del stock, sobre los inventarios de la organización. Para fines de la presente investigación, se optó por hacer uso de un método con enfoque cualitativo; ya que, recolectando datos e información, las hipótesis pasan a un plano real y comprobable. En base a la investigación de campo, se corrobora que la Empresa Comercial ¨Alejo¨ no posee un adecuado sistema de control de inventarios, generando así que se proponga un sistema factible para dicha empresa, con la finalidad de mejorar el procedimiento de registro de inventarios, así como la reducción de gastos bajo el propósito de fortalecer la rentabilidad.
Keywords: CONTROL DE INVENTARIOS; INVENTARIOS; CONTROL INTERNO; EMPRESA